We are given the equation of a parabola. Let's remember the general form for this equation:
![y=ax^2+bx+c](https://img.qammunity.org/2023/formulas/mathematics/high-school/g7mvpjunjwe6qob7ddy7l4f0glbtdi9gci.png)
The given equation is:
![y=x^2+10x+8](https://img.qammunity.org/2023/formulas/mathematics/college/deo5z88mklbf028mny86yk37jai10j67vp.png)
Therefore, the coefficients are:
![\begin{gathered} a=1 \\ b=10 \\ c=8 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/fkn2gemqzy9dnle9870pm72f6dnko17c2t.png)
Now we will rewrite the equation to the form:
![y=(x-h)^2+k](https://img.qammunity.org/2023/formulas/mathematics/high-school/h4kqjwwshdhi39of5qh206bvx52ti58zvg.png)
First we will change the equation in the following way:
![y=x^2+10x+25-17](https://img.qammunity.org/2023/formulas/mathematics/college/evht5ngqhidcoarzuxs3arbsmdu8so23jh.png)
Now we can factor:
![y=(x+5)^2-17](https://img.qammunity.org/2023/formulas/mathematics/college/l8fqah16wakjex7w16mtlnzfnbw1sdcpma.png)
since the term (x+5)^2 is multiplied by a positive constant, this means that the parabola opens up.
The vertex of the parabola is the point (h,k), in this case, we have:
![(h,k)=(-5,-17)](https://img.qammunity.org/2023/formulas/mathematics/college/mxi5ky1mx4utfh1qw6nuob4fvjechi4ign.png)
The axis of symmetry for a parabola is x = h, therefore, the axis of symmetry for this parabola is:
![x=-5](https://img.qammunity.org/2023/formulas/mathematics/high-school/pexczrieq35nou059rt5i81ydups7s2uzi.png)
The y-intercept is the point where x = 0, therefore, making x zero in the equation we get:
![\begin{gathered} y=(x+5)^2-17 \\ y=(0+5)^2-17 \\ y=25-17=8 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/x2qx6ddld4u7q1skx8tlhi62z84reczk4n.png)
Therefore the y-intercept is y = 8.